ANALISIS PENERAPAN METODE PENCATATAN AKUNTANSI BERBASIS CASH PADA TRANSAKSI-TRANSAKSI CV. TIGA PERMATA (AGEN BRILINK) - Ayu Putri Pramita; Soesilawati Soema Atmadja (Ekomania, 2023)
The accounting basic is an important proof in the recording. The cash basis is the accounting policy that recognizes the effect of transactions and other events when cash or its equivalent is received or paid as a confirmation of income or income, financing and expenses, assuming that the recognition will be made when cash is received or paid. received or money is spent. † The aim of this study was to analyze the application of cash accounting methods to the transactions in the CV. Tega Permata (BRILink's agent). To achieve these goals, the authors use the observation method and interviews with a qualitative approach to learn how to apply the accounting registration methods used in the company. Three gems (BRILink factor) not too big. With this method it is also possible to know clearly the financial position of the company at that time. The principle of the BRILink agent is nothing but fee sharing, this principle is very relevant when using this cash basis method.